2015
DOI: 10.1099/jgv.0.000280
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of type I and type III IFN signalling by NSs protein of severe fever with thrombocytopenia syndrome virus through inhibition of STAT1 phosphorylation and activation

Abstract: Severe fever with thrombocytopenia syndrome virus (SFTSV) is an emerging tick-borne pathogen causing significant morbidity and mortality in Asia. NSs protein of SFTSV is known to perturb type I IFN induction and signalling, but the mechanism remains to be fully understood. Here, we showed the suppression of both type I and type III IFN signalling by SFTSV NSs protein is mediated through inhibition of STAT1 phosphorylation and activation. Infection with live SFTSV or expression of NSs potently suppressed IFN-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 49 publications
4
50
2
Order By: Relevance
“…HEK293T cells transiently expressing untagged or V5-tagged UUKV, HRTV, or SFTSV NSs proteins were treated with recombinant IFN-β for 30 min, and the cell lysates were harvested for Western blotting 24 h posttransfection. Unlike Chaudhary et al (33), we observed no difference in the levels of STAT1 or phosphorylated STAT1 (at position Ser727 or position Tyr701) in the presence of SFTSV NSs compared to the mock control. Similar results were observed for UUKV and HRTV NSs proteins (Fig.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…HEK293T cells transiently expressing untagged or V5-tagged UUKV, HRTV, or SFTSV NSs proteins were treated with recombinant IFN-β for 30 min, and the cell lysates were harvested for Western blotting 24 h posttransfection. Unlike Chaudhary et al (33), we observed no difference in the levels of STAT1 or phosphorylated STAT1 (at position Ser727 or position Tyr701) in the presence of SFTSV NSs compared to the mock control. Similar results were observed for UUKV and HRTV NSs proteins (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…Other published data show that SFTSV NSs directly interacts with and sequesters STAT1 and STAT2 into inclusion bodies to block type I IFN signaling (33, 34). To investigate whether HRTV NSs was also capable of these interactions, we performed immunoprecipitation of transfected V5-tagged NSs proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The tripartite genome is comprised of the S, M, and L segments, which encode the nucleocapsid, glycoproteins, and RNA-dependent RNA polymerase, respectively. In addition to the structural proteins, some bunyaviruses, including SFTSV, also encode non-structural proteins that antagonize host innate immune mechanisms [1619]. The viral glycoproteins G N and G C form a heterodimer on the surface of virions, and are both necessary and sufficient for viral entry [15].…”
Section: Introductionmentioning
confidence: 99%